2021
DOI: 10.1111/sms.14033
|View full text |Cite
|
Sign up to set email alerts
|

Generalized bioelectric impedance‐based equations underestimate body fluids in athletes

Abstract: The current study aimed: (i) to external validate total body water (TBW) and extracellular water (ECW) derived from athlete and non‐athlete predictive equations using radioisotope dilution techniques as a reference criterion in male and female athletes; (ii) in a larger sample, to determine the agreement between specific and generalized equations when estimating body fluids in male and female athletes practicing different sports. A total of 1371 athletes (men: n = 921, age 23.9 ± 1.4 y; women: n = 450, age 27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Body mass index (BMI) was calculated as total body mass (kilograms) divided by height (meters) squared. BIA was performed according with standardized procedures specific for athletes [ 9 ]. The bioelectrical phase angle was directly measured with BIA (BIA 101, Akern, Florence, Italy), which applies an alternating current of 800 μA at a single frequency of 50 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body mass index (BMI) was calculated as total body mass (kilograms) divided by height (meters) squared. BIA was performed according with standardized procedures specific for athletes [ 9 ]. The bioelectrical phase angle was directly measured with BIA (BIA 101, Akern, Florence, Italy), which applies an alternating current of 800 μA at a single frequency of 50 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the portability and ease of application, the use of the bioelectrical impedance analysis (BIA) has been increasing in sports practice especially because current studies have revealed that when following standardized protocols for BIA assessment, body composition measurements are comparable to more sophisticated clinical methods [ 7 , 8 , 9 , 10 ]. In addition, BIA yields additional raw bioelectrical parameters that can be independently used to qualitatively track body composition [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods for assessing body composition, bioelectrical impedance analysis (BIA) has recently gained relevance, especially in soccer [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], where field and user-friendly methods are warranted [ 16 ]. Through the measurement and use of bioelectrical resistance (R) and reactance (Xc) in predictive equations, quantification of a wide range of body composition parameters is possible [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the resistance and reactance of each tissue, different body composition components can be determined. To date, several predictive equations have been developed considering different populations (Campa et al, 2021;Coratella et al, 2021), and importantly different predictive equations provide different outcomes when used on the same subjects (Pichard et al, 1997;Coratella et al, 2021). Therefore, an accurate choice of predictive formulas is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their body composition features, some exercisers could not have the requisites to be defined as athletes, and consequently body composition might be estimated less accurately using equations developed for the general population. In this regard, the error would derive from the fact that a group of exercisers, having similar body composition characteristics to those of the subjects involved in the studies that have validated the formulas for athletes, would result in greater accuracy when equations for athletes are used (Coratella et al, 2021). Unfortunately, body composition characteristics cannot be discovered until a method of analysis is applied.…”
Section: Introductionmentioning
confidence: 99%